2022
DOI: 10.1002/adma.202110252
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Potential Diagram Guided Rational Tuning of Electrical Properties: A Case Study of CsPbBr3 for X‐ray Detection

Abstract: Controlling the carrier polarity and concentration underlies most electronic and optoelectronic devices. However, for the intensively studied lead halide perovskites, the doping tunability is inefficient. In this work, taking CsPbBr3 as an example, it is revealed that the coexistence of metallic Pb or CsBr3/Br2, rather than the precursor ratio, can provide Pb‐rich/Br‐poor or Br‐rich/Pb‐poor chemical conditions, enabling the tunability of electrical properties from weak n‐type, intrinsic, to moderate p‐type. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…Lead halide perovskites of ABX 3 (A = MA + , Cs + ; B = Pb 2+ , X = Cl – , Br – , I – ) have been widely studied due to their promising optoelectronic applications such as such as solar cells, light-emitting diodes, lasers, X-ray detectors, and scintillators. , However, lead-based halide perovskites are often unstable and easily hydrolyzed. Meanwhile, the toxicity of lead limits their applications . Thus, it is urgent to develop alternative lead-free perovskites with photoelectric properties similar to those of lead-based perovskites.…”
mentioning
confidence: 99%
“…Lead halide perovskites of ABX 3 (A = MA + , Cs + ; B = Pb 2+ , X = Cl – , Br – , I – ) have been widely studied due to their promising optoelectronic applications such as such as solar cells, light-emitting diodes, lasers, X-ray detectors, and scintillators. , However, lead-based halide perovskites are often unstable and easily hydrolyzed. Meanwhile, the toxicity of lead limits their applications . Thus, it is urgent to develop alternative lead-free perovskites with photoelectric properties similar to those of lead-based perovskites.…”
mentioning
confidence: 99%
“…[32,33] According to a previous study, CsBr 3 could provide a Br-rich environment, which benefits Br − vacancy restraint. [34] In light of the above analysis, the crystal structure of Cs 4 PbBr 6 is diagramed in Figure 1i and Cif 1, where [PbBr 6 ] 4− octahedra array was isolated by Cs + ion.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in Figure a,b, the single peak at 402.2 eV of the N 1s core level observed in the spectrum of NCs with DD 10 AB post-treatment gives clear evidence for the existence of DDA + on the NC surface . The shoulder peaks locked at 136.6 and 141.4 eV are attributed to the undercoordinated Pb for pristine-CsPbBr 3 NCs, which would lead to the formation of Br vacancies . On the contrary, it is observed that the shoulder entirely disappears in the spectrum of DD 10 AB-CsPbBr 3 NCs, indicating that Pb 2+ is coordinated with Br – stemming from DD 10 AB, and thus, Br vacancy is effectively passivated, resulting in an improved stability of NCs with higher PLQY.…”
Section: Resultsmentioning
confidence: 99%